Influence of spatial and temporal distribution of Turbulent Kinetic Energy on heat transfer coefficient in a light duty CI engine operating with Partially Premixed Combustion. (25th January 2018) - Tanov, Slavey; Pachano, Leonardo; Andersson, Öivind; Wang, Zhenkan; Richter, Mattias; Pastor, José V.; García-Oliver, José M.; García, Antonio
Highlights: Heat transfer coefficient for gasoline PPC is assessed. Heat transfer coefficient considers experimentally derived flow field parameters. High TKE levels at bowl periphery and center due to fuel injection and combustion. The greatest differences respect to motored case observed with single injection. Abstract: Emission regulations together with the need of more fuel-efficient engines have driven the development of promising combustion concepts in compression ignition (CI) engines. Most of these combustion concepts, lead towards a lean and low temperature combustion potentially suitable to achieve lower emission and fuel consumption levels compared to conventional diesel combustion. In this framework, Partially Premixed Combustion (PPC) using gasoline as fuel is one of the most accepted concepts. There are numerous studies focused on studying concepts such as PPC from the emissions point of view. Nonetheless, there is a lack of knowledge regarding changes in heat transfer introduced by the use of these combustion concepts. It is worth noting that heat transfer can be considered as a key aspect behind possible engine performance improvements. Thus, the reliable estimation of this parameter is of considerable importance. Additionally, a better understanding of how events such as injection and combustion might affect heat transfer is also relevant. To gain insight into gasoline PPC heat transfer coefficient, its evolution during late compression and early expansion were studied. In particular, this work aims to analyze Turbulent Kinetic Energy (TKE) spatial and temporal evolution influence on heat transfer coefficient. The analysis is based on experimental TKE maps derived from Particle Image Velocimetry (PIV) data. For the heat transfer coefficient estimation a modified Woschni correlation has been used. Results from several injection strategies and a reference motored case have been analyzed. It has been found that injection strategy has a considerable influence on the TKE field and hence on heat transfer coefficient evolution.